Signing electronic contracts. - Molnar, David (Crossroads :the ACM student magazine.)
Electronic commerce faces the problem of signing electronic contracts. Three approaches for handling electronic contracts include 1) no trusted third party protocols, 2) strongly-trusted third party protocols and 3) weakly-trusted third party protocols. A secondary problem facing electronic commerce is self-enforcing contract design.